Pengembangan Sistem Kendali Sepeda Statis Berbasis Ergonomi Dengan Menggunakan Metode Reverse Engineering - Fadhil Fadhil mubaroq; Muhammad Risky Alida Nuris; Hery Irwan (Jurnal Teknik Ibnu Sina (JT-IBSI), 2025)
A stationary bike is a popular exercise tool, but its design often lacks ergonomics, leading to discomfort and potential injury for users. This research aims to develop a more ergonomic control system for stationary bikes using reverse engineering methods. This method is used to analyze existing stationary bike designs, identify ergonomic issues, and design better improvisations. The results of the reverse engineering analysis indicate several ergonomic problems in the analyzed stationary bike design, such as a lack of flexibility in position adjustment and a design that does not align with the users' anthropometric data. Based on these analysis results, a new, more ergonomic control system has been designed, including features for more flexible position adjustments and a design tailored to the users' body dimensions. From the initial survey conducted, users complained about the difficulty of converting a regular bike into a stationary bike, with many expressing concerns about the high cost of stationary bikes that are not efficient. Addressing these issues, the author attempts to design a tool or product that transforms a regular bike into an ergonomic, cost-effective stationary bike. A significant factor in the design of this product is the ergonomic aspect, which involves studying human factors in the design process, including anatomy, psychology, physiology, engineering, management, and design.